2022
DOI: 10.3390/nano12030495
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Bolometric Responses of MoS2 Nanoflowers and Multi-Walled Carbon Nanotube Composite Network

Abstract: Due to their broadband optical absorption ability and fast response times, carbon nanotube (CNT)-based materials are considered promising alternatives to the toxic compounds used in commercial infrared sensors. However, the direct use of pure CNT networks as infrared sensors for simple resistance read-outs results in low sensitivity values. In this work, MoS2 nanoflowers are composited with CNT networks via a facile hydrothermal process to increase the bolometric performance. The thermal diffusivity (α) agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…In this work, the suspended length of S7 is 1.22 mm. If the sample suspending length is reduced to 200 μm in the future (the typical size of the pixel unit of a bolometer array), the response time of CAF will be reduced to 1/37 of the original response time, corresponding to 2.95–3.03 ms (framing rate of 330–339 per second). This short response time is due to the ultra-low density of CAF, which is comparable or shorter than the reported response time for MWCNT films (1–2.5 ms), SWCNT films (40–50 ms), and a-Si (11–500 ms) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the suspended length of S7 is 1.22 mm. If the sample suspending length is reduced to 200 μm in the future (the typical size of the pixel unit of a bolometer array), the response time of CAF will be reduced to 1/37 of the original response time, corresponding to 2.95–3.03 ms (framing rate of 330–339 per second). This short response time is due to the ultra-low density of CAF, which is comparable or shorter than the reported response time for MWCNT films (1–2.5 ms), SWCNT films (40–50 ms), and a-Si (11–500 ms) .…”
Section: Resultsmentioning
confidence: 99%
“…Fast and sensitive infrared (IR) detectors that operate at room temperature are in great demand in various applications such as security, environmental monitoring, remote control, biomedical applications, optical communications, and thermal imaging as well as cutting-edge technologies like smart automobiles and robotic navigation. Novel nanomaterials such as ZnS, MoS 2 , and WS 2 have been developed for achieving fast, sensitive, and flexible photodetectors in recent years. Carbon based materials have the advantages of wideband absorption, fast response, good electrical conductivity, low cost, good stability, etc., which have gained great attention as one of the most promising materials for flexible infrared detectors. Lu et al reported an absolute temperature coefficient of resistance (TCR) of 0.17%/K for single-walled carbon nanotube (SWCNT) films and 0.07%/K for multi-walled carbon nanotube (MWCNT) films . John et al.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of MoS 2 added a synergistic effect to the bolometric response by influencing the intertube junctions (leading to a great deal of phonon scattering) and enhancing the optical absorption. 191 Finally, apart from functionalization and using semiconducting nanoparticles (NPs), metal NPs (in particular, Au) have also been used to improve the bolometric response of MWCNT film. 40 recently, studies have also been performed on 3D CNT structures for bolometric IR sensor arrays.…”
Section: { }mentioning
confidence: 99%
“…Copyright 2020, American Chemical Society, Washington, DC. Panel (f) was reproduced with permission from ref . Copyright 2022.…”
mentioning
confidence: 99%
See 1 more Smart Citation